2023
DOI: 10.7150/thno.79806
|View full text |Cite
|
Sign up to set email alerts
|

Radiopharmaceuticals heat anti-tumor immunity

Abstract: Radiopharmaceutical therapy (RPT) has proven to be an effective cancer treatment with minimal toxicity. With several RPT agents approved by FDA, the remarkable potential of this therapy is now being recognized, and the anti-tumor immunity induced by RPT is beginning to be noticed. This review evaluates the potential of RPT for immune activation, including promoting the release of danger associated-molecular pattern molecules that recruit inflammatory cells into the tumor microenvironment, and activating antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…In the field of research on antitumor drugs, there has been a growing interest in the efficacy of various compounds, including PTX [ 133 ], cephalexin (CPT) [ 133 ], irinotecan hydrochloride (CPT-11) [ 134 ], and topotecan hydrochloride (TPT) [ 135 ]. These drugs have gathered attention due to their potential therapeutic benefits, in addition to DOX.…”
Section: Research On Polysaccharide-aunps As Drug Delivery Carriersmentioning
confidence: 99%
“…In the field of research on antitumor drugs, there has been a growing interest in the efficacy of various compounds, including PTX [ 133 ], cephalexin (CPT) [ 133 ], irinotecan hydrochloride (CPT-11) [ 134 ], and topotecan hydrochloride (TPT) [ 135 ]. These drugs have gathered attention due to their potential therapeutic benefits, in addition to DOX.…”
Section: Research On Polysaccharide-aunps As Drug Delivery Carriersmentioning
confidence: 99%
“…Therefore, there is great potential for labeling antibodies or aptamers to MUC1 with radionuclides, which could enhance the therapeutic effect of drugs for cancer treatment [183]. Compared to traditional treatment methods, radiopharmaceutical therapy (RPT) is the least toxic and most targeted form of effective cancer treatment [184,185]. Although RPT has been shown to be an effective cancer treatment and has been clinically studied for over 40 years, it has not become part of the cancer treatment armamentarium like other therapies [184].…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
“…Radiotherapy is a powerful therapeutic modality of cancer which can kill tumor cells through direct DNA damage and indirect reactive oxygen species (ROS) damage without tissue penetration limitation [ 6 , 26 , 27 , 28 ]. Recently, it has been reported that RT can induce ICD with TAA and DAMP release, thereby triggering DC maturation and eliciting antitumor immune responses [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. It is widely reported that the coordinated high-order metal elements in nanocrystals can induce tumor ICD via radiotherapy.…”
Section: Radiotherapymentioning
confidence: 99%